The mononuclear phagocyte system: tissue resident macrophages - activation and regulation - Gordon, Siamon (Henry Stewart Talks, 2021)
Macrophages in human disease, Macrophage receptors and interactions, Differential activation of macrophage, Tissue macrophage heterogeneity, Macrophage fusion and differentiation, Macrophages and cancer, Regulation of macrophages